Microbial assessment of dental unit waterlines in an institutional setup in Karnataka, South India - Shobha Rodrigues (Indian Journal of Dental Research, 2017)
Background and Aim: Biofilms in dental unit waterlines (DUWLs), suction hoses, and fittings are a potentially significant source of cross-contamination posing significant health risk as these may come into contact with patients during treatment. The purpose of this in vitro study was to identify the spectrum of bacterial flora colonizing the DUWLs and to detect pathogenic microorganisms present in such an environmental niche. Materials and Methods: Thirty DUWL samples were collected from in use dental units selected randomly from various clinical departments. Samples were collected from the following devices; 3-in-1 syringe waterline, section of waterline tubing supplying the 3-in-1 syringe, and the air rotor water. The samples were subjected to bacteriological analysis, and all bacterial isolates were tested for their ability to form biofilms. Results: A descriptive analysis of the results obtained was carried out, and it was observed that 7 out of 30 (23.3%) samples collected from DUWL were supplying water of unsatisfactory quality with species of low-pathogenicity bacteria isolated present in significant numbers; four of ten (40%) water supply lines contained bacterial biofilms; and the species with greatest capability to form biofilms were Enterobacter species (spp.). In addition, the results were also subjected to Chi-square test which revealed no statistical difference between the species and the location of collection of samples. Conclusion: Within the limitations of this study, it is concluded that DUWLs are not totally free of contamination. Microbial biofilms are a significant source of cross-contamination and cross-infection in the dental clinic environment.